Perhitungan Harga Pokok Produksi Perusahaan Jasa Kurir Studi Kasus PT Pos Indonesia (Persero) - Suharti, Sri (EKUBIS: Jurnal Ekonomi, Keuangan, & Bisnis, 2020)
The calculation of production cost is the most fundamental aspect for every company. Production cost will be a baseline to determining selling price of goods or service that influence company’s capability to compete with competitors. Thus, determine the right method for calculate the production cost is an important process for the company which has to be aligned with company’s condition and business strategies. PT. POS Indonesia as a Logistic Service Provider company has a lot of joint cost and involves departments from different places. In conclusion, using full costing method and actual cost system to calculate their production cost are the best method for this company.